Perancangan Game Edukasi Untuk Meningkatkan Pemahaman Belajar Siswa Kelas V SD Tentang Pendidikan Kewarganegaraan Berbasis Android - Nur Rambu Madik Anawaru; Yustina Rada; Tri Sari Dewi Novyanti Bertha Mira (STIKes Ibnu Sina Ajibarang, 2024)
The Mburukulu Elementary School in Mburukulu Village, Pahunga Lodu District, East Sumba Regency, is facing challenges in teaching Citizenship Education (PKN) in class V. The lack of interaction between teachers and students and the lack of student involvement has resulted in boredom, lack of focus, and lack of enthusiasm in Study. This research aims to create and implement an interactive educational game entitled